Protecting Emergency Responders, Volume 4 Personal Protective Equipment Guidelines for Structural Collapse Events - Willis, Henry H. (RAND Corporation, 2006)
This monograph serves as a technical source for National Institute for Occupational Safety and Health (NIOSH) incident commander guidelines for emergency response immediately following large structural collapse events. It gives guidelines for personal protective equipment (PPE), focusing on required modifications to responders' typical PPE ensembles because of the duration of response and the need to prevent exposures to likely hazards from pathogens, airborne dusts, and gaseous hazardous materials.